Pengelolaan Manajemen SDM dalam Meningkatkan Kesejahteraan & Kinerja Karyawan di Era Transformasi Digital - Anisa Tanasya; Annisya Adelia Pratiwi Aalamsyah; Mulyadi Mulyadi; Soendra Kurnia Ilaihi; Yusuf Roni (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study discusses the strategy of human resource management (HRM) in addresing the challenges of digital transformation and its impact on employee welfare and performance. Digital transformation has become aa necessity to improve efficiency and competitiveness. Based on interviews with management and employees at YAISGO Logistic, it is found that the company has implemented several initiatives, such as the development of digital competencies for employees, digitalizing the recruitment process, and the application of an HR management system. These steps contribute to enhancing work efficiency, service quality, and data management. However, the implementation of digital transformation also faces several challenges. Some of these include resistance to change, an imbalance between work demands an employee welfare, and concerns about data security and privacy. The results of the study indicate that the succsess of digital transformaation is not only determined by the technology used but also by the readiness and adaptability of human resources. Responsive, fair, and welfare-oriented HR management is key to optimizing employee performance.